LIPOPROTEIN APHERESIS: YESTERDAY, TODAY, TOMORROW. REVIEW - U. Julius; S. Tselmin; S. R. Bornstein (Российский кардиологический журнал)
The first attempts to treat patients with homozygous familial hypercholesterolemia (HCH) were performed in the 60ies and 70ies using a total plasma exchange. Later on, more specific lipoprotein apheresis (LA) methods have been developed – the replacement with foreign proteins was no longer necessary. It could be demonstrated that LA is life-saving in these patients, lipid-lowering drugs were shown to be much less effective than in other HCH patients. A severe HCH became an accepted indication for LA when cardiovascular events appeared. An elevation of Lipoprotein(a) (Lp(a)) is an internationally accepted independent atherogenic risk factor. Thus, an increasing number of patients with high Lp(a) concentrations suffering from life-threatening cardiovascular events like a myocardial infarction or a stroke started to be treated extracorporeally. Russian specific PocardR anti-Lp(a) columns are produced, their position within the LA methods is discussed. In the future, an antisense oligonucleotide against apolipoprotein(a) will represent another therapeutic option.